[Ang titser ; Bad start for art : Start, young goons - Lazaro, Cheche (The Probe Team, 1991)
Investigates the project action of teachers : a jazz band's performance in Calapan, Mindoro on September 1990 ending up with physical injuries of the members ; and the junior police in Manila.